Comércio internacional e meio ambiente: estímulo à produção sustentável ou mero protecionismo comercial a posição do Brasil em dois casos de litígio - Luz, Lília Silva (2012)
The World Trade Organization (WTO) was established in 1994 as a result of the Uruguay Round, and has as its principal aim advocate for the maintenance of free trade between nations. The preamble of its Constitutive Agreement specifically cites as an institution the goal of achieving sustainable development and the pursuit of protecting and preserving the environment, bringing into the sphere of world trade the idea that concern for the environmental cause is not restricted only the group of environmentalists, but rather has entered the economic landscape in a way not only ideological, but also pragmatic. The General Agreement on Tariffs and Trade (GATT) 1947, part of the GATT 1994, contains a device that allows the adoption of trade restrictive measures, provided that such measures aimed at protecting the environment - Article XX. The Settlement Body (DSB) is part of the WTO and acts in dissolving disputes between the countries motivated by trade. It examines two cases where countries have imposed restrictive trade measures with environmental justification. The first case was closed in 1996, with award of damages given to Brazil, on the breakdown of U.S. environmental legislation imposed on imported gasoline from Brazil - and the second, begun in 2005 and closed in 2007, coming out victorious again Brazil is on the import ban on retreaded tires to Brazil. The objective is to answer the question: how the environment is treated in the midst of trade discussions - which is aimed at its protection or its use with economic objectives in disguise? For the preparation of this work, extensive documentary research was undertaken with the virtual site of the WTO to review the entire production of legal cases and subsequent analysis of the key issue for the work, and literature of authors who have studied the tense relationship between trade international environment. The first case, it could be seen that the political movement performed by the U.S. with the aim of achieving acceptable standards of air quality was an institutional effort to ensure the quality of air, and thus would be inappropriate to say that the regulation of gasoline was merely a disguised trade barrier.However, a careful analysis of the implementation and operation of gasoline regulation may reveal intentions disguised trade and U.S. environmental argument did not hold. The weight of this environment was relegated, since there were clearly outside interests to the environmental cause. The second case, it was realized that, despite clear attempts by the EC to promote ecological dumping, send when brought to Brazil, supposedly a country with weaker environmental structure on surveillance, a residue that, pursuant to internal policies, as could not be sent to their own landfills, the Brazilian discourse remained focused on the environmental cause, and this sort there was the existence of disguised trade barriers, but of importance, at least a priori, the discussion of foreign forces on the environment environment because there is no way to legally justify the reversal of the total understanding of the first judging body, the sight of all the arguments presented by Brazil and the nonsubmission of new facts upon appeal. Still, quite heartening to reflect on the role of trade liberalization on the environment in general, because, while they do not reach a definitive conclusion will reveal positions in both directions, both for and against, the that only adds to the discussions and makes this a very fertile topic for future research